Una mirada técnica de la naturaleza - Joan F. Mateu Bellés; Iván Portugués Mollá (Cuadernos de Geografía de la Universitat de València)
Studies of dams require detailed river explorations from the planning phase. This paper analyses El Reconocimiento del río Cabriel [The Reconnaissance of the Cabriel river] (1941) by Luis Janini Cuesta, who was attached to the Confederación Hidrográfica del Júcar. This was a preliminary document which summarized the engineer?s task during his itinerary along the river from the headwaters to the confluence with the Júcar river. The aim of the journey was the identification of the most suitable locations for reservoirs. This technical view ignored other natural values of the Cabriel river.